Professor, aluno e livro didático em aulas de ciências : análise retórica dos argumentos didáticos - Ossak, Ana Lídia (2006)
This project presents a study concerning the rhetoric constituted between the teacher (speaker), his students (auditorium) and the textbook (logos) in a situation of sciences teaching. The objective was to investigate how the knowledge of the textbook of sciences, talking about the nutrition of the plants, were given for children of 6th grade of the Elementary School. We examined the rhetorical resources used by the teacher to know the reach of the scientific arguments among the children. The methodological procedures were based on qualitative approach. We based ourselves in Reboul (1975; 2004), Contenças (1999), Lakoff and Johnson (2002), Breton (2003) and Perelman (2004; 2005). We analyzed the rhetoric illustrations from the textbooks used by the teacher and the present illustrations in the argumentative dynamics with his students, in three classes recorded during the month of October of 2005. In the constitution of the arguments that presented a model of nutrition and physiology of the plants we pointed the presence of illustrations like metaphor, metonymy, sinédoque and other resources. As a result of the investigation we highlighted that: a) the teacher is driven by the objectives of the textbook to execute his pedagogic work. He accomplishes the conceptual reconstruction, going from the private to the general, from metonymy to sinédoque (the possible materialization of the nutrition model); b) the students accomplish a contrary movement, they go from the general definition (sinédoque) to the metonymies and the metaphors; they want to discuss the singularities of the plants. We conclude that, in the classroom, the teacher and the students follow opposite ways. The first one follows the logos of the textbook; the students stay between the lessons, the logos, of the textbook (and of the teacher) and their own knowledge about some characteristics of the plants. It doesn't happen a construction of the conceptual model of the plants nutrition among the students, because of the hegemony of the logos of the textbook about the teacher and the students. In the spite of the teacher's attempt in reaching his objective - to show his students a conceptual model of the nutrition of the plants -, the classes are based just in the textbook and it doesn't assist the learning goals about the nutrition, even though, the model that presents (and guides the teacher) is elaborated in terms of a general communication on the biological processes.